Joint toxicity of copper and diazinon during embryonic and larval development of the common South American toad, Rhinella arenarum - Aronzon, Carolina Mariel (2016)
Copper (Cu) and diazinon are two widely distributed pollutants; they coexist in agro-ecosystems and cause toxicity to wild biota. This study proposes to analyse the joint toxicity of binary mixtures of Cu and diazinon on the early development of the South American toad, Rhinella arenarum by means of a standardised test. Cu was always more toxic than diazinon. Cu was more embryotoxic while the pesticide was more toxic during the larval exposure than during the embryonic period. The different Cu/diazinon mixtures proportions assayed were significantly less toxic than expected by additive effects. Thus, an antagonistic interaction pattern was observed. This pattern was independent of the assayed proportion, the exposure times and the exposure developmental periods. In the risk assessment analysis to establish water quality criteria, the joint toxicity should be considered at different ratios, exposure time and life period for a certain species, in order to preserve wild species.